Soil Nutrient Dynamics under Old and Young Cocoa, Coffee and Cashew Plantations at Uhonmora, Edo State, Nigeria - Ipinmoroti, Rotimi Rufus; Ogeh, Joseph Sunday (JOURNAL OF TROPICAL SOILS, 2014)
A study was conducted to assess nutrient dynamics of soils under old and young cocoa, coffee and cashew plantations and the leaf nutrient contents of the crops at Uhonmora, Edo State, Nigeria for proper cultural and soil fertility management of the plantations. Soil and crop leaf samples were collected from each plantation using a random sampling technique. The samples were analyzed using standard procedures for sand, silt, clay, pH (H2O), electrical conductivity (EC), total N, available P, K, Ca, Mg, Na, and Effective Cation Exchange Capacity (ECEC). Leaf samples were analyzed for N, P, K, Ca, Mg and Na. Data were compared with the corresponding soil and foliar critical nutrient values for each crop. Results indicated that the soils were texturally sandy clay loam and acidic. The soils varied in their nutrient contents, with soil P for the old cocoa, young coffee and cashew plantations far below critical values. The young cashew plot was low in N content but adequate for other plots. However, the soil ECEC increased with the increasing of calcium contents. Leaf N was below critical for all the crops. Leaf K was low for cocoa and coffee plants, leaf Ca was low for the young cashew plants, while leaf Mg was low for the young cocoa and old cashew. The high soil Mg/K ratio of 8.7- 22.3 as against the established value of 2.0 might have resulted in gross nutrient imbalance which must have affected the absorption and utilization of other nutrients. Hence, adequate soil N did not translate the same availability to the crops. The ECEC showed that the soil needs to be improved upon for sustainable productivity. Soil nutrient content variation across the plantations with age of establishment will necessitate the need for consistent routine soil nutrient assessment for proper and balanced soil nutrient supply to the crops, for healthy crop growth and optimum yield. Management practices of soil surface mulching using organic wastes and cover crops under compatible cropping systems are needed for successful plot establishment and better growth performance of the young seedlings.Key words: Nutrient dynamics, plantation crops, rehabilitation, soil fertility management [How to Cite: Rotimi RI and JS Ogeh. 2014. Soil Nutrient Dynamics under Old and Young Cocoa, Coffee and Cashew Plantations at Uhonmora, Edo State, Nigeria. J Trop Soils 19(2): 85-90. Doi: 10.5400/jts.2014.19.2.85] [Permalink/DOI: www.dx.doi.org/10.5400/jts.2014.19.2.85]